Property market liquidity and REIT liquidity - David H. Downs; Bing Zhu (Real Estate Economics, 2022)
This study examines the asset–stock liquidity relationship for firms with location-specific assets. Using a sample of real estate investment trusts (REITs), we extend the concept of asset liquidity to include information based on local property market turnover. Our findings confirm that holding more cash increases REIT stock liquidity. More importantly, we find a positive relation between property market liquidity and REIT stock liquidity. This relation is stronger for REITs with lower growth opportunities, less information advantage, and greater financial constraints. Our findings also provide evidence that managers can actively influence stock liquidity through asset structure.
Keywords: 330; geographic asset location; liquidity; real estate returns